DAYA DUKUNG DAN INDEKS DAYA DUKUNG HIJAUAN ALAMI DI AREAL PERKEBUNAN KELAPA DALAM SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Wenno, Adriani; Patty, C H. W; Eoh, Marna (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
The purpose of this study was to determine carrying capacity and carrying capacity index of natural forage as ruminant feed, and to determine botanical compositions and forage production in the coconut plantation area, District of Taniwel, Western Seram Regency. Primary and secondary data were collected, and data collection was conducted by using purposive sampling method. Variables measured included botanical composition, forage production, forage carrying capacity, and carrying capacity index of natural forage. The results showed that 64,81% of forage botanical composition was grass, 26,47% was weeds, and 10,52% was legumes. The carrying capacity of native forage in the coconut plantation area was 1.515 ruminants for fresh forage and 1.177 for forage dry matter, while carrying capacity index of native forage was 2 indicating unsafety level of forage available for ruminant feeding.